Glazed brick decoration in the Ancient Near East : proceedings of a workshop at the 11th International Congress of the Archaeology of the Ancient Near East (Munich) in April 2018 : for the Vorderasiatisches Museum - Staatliche Museen zu Berlin - Fügert, Anja,; Gries, Helen, (Archaeopress Archaeology, 2020)
Glazed bricks applied as a new form of colourful and glossy architectural decor first started to appear in the early Iron Age on monumental buildings of the Ancient Near East. This volume provides an updated overview of the development of glazed bricks and scientific research on the topic.